Hubungan Kunjungan Antenatal Care dan BBLR dengan Kejadian Stunting pada Balita Usia 24-59 Bulan: The Relationship between Antenatal Care and BBLR Visits and Stunting Incidence in Toddlers Aged 24-59 Months - Ika Wahyu Ningsih; Novita Eka Kusuma W.; Rijanto; Kharisma Kusumaningtyas (Gema Bidan Indonesia, 2025)
Stunting is a condition where a child fails to grow properly due to chronic malnutrition, resulting in a shorter stature compared to other children of the same age. This research aims to analyze the correlation between antenatal care visits and low birth weight (LBW) history with the incidence of stunting in children aged 24 to 59 months.The research uses an analytical observational method with a cross-sectional approach. The population consists of mothers and children aged 24 to 59 months at Balas Klumprik Health Center, totaling 841 toddlers. The sample includes 89 mothers and stunted toddlers, selected through simple random sampling. The independent variables are antenatal care visits and LBW history, while the dependent variable is stunting. The instrument used in this study is the analysis using the Maternal and Child Health (MCH) book. The correlation is analyzed using the Chi-Square test. The results show that almost all respondents (77.5%) comply with antenatal care. Nearly all respondents (95.5%) are not stunted. The Chi-Square test results show a P-Value of 0.000, where p < α 0.05, indicating a correlation between antenatal care visits and the incidence of stunting in children aged 24 to 59 months. The Chi-Square test results also show a P-Value of 0.001, where p < α 0.05, indicating a correlation between LBW history and the incidence of stunting in children aged 24 to 59 months in the Balas Klumprik Health Center area. The conclusion of this research is that there is a correlation between antenatal care visits and LBW history with the incidence of stunting. The recommendation for the Balas Klumprik Health Center is to conduct socialization for pregnant women about the importance of antenatal care during pregnancy. For the community, it is hoped that there will be an increased awareness of the importance of nutritional needs for toddlers.